1996
DOI: 10.1002/j.1460-2075.1996.tb00635.x
|View full text |Cite
|
Sign up to set email alerts
|

The Epstein-Barr virus bZIP transcription factor Zta causes G0/G1 cell cycle arrest through induction of cyclin-dependent kinase inhibitors.

Abstract: While oncoproteins encoded by small DNA tumor viruses and Epstein‐Barr virus (EBV) latent antigens facilitate G1/S progression, the EBV lytic switch transactivator Zta was found to inhibit growth by causing cell cycle arrest in G0/G1 in several epithelial tumor cell lines. Expression of Zta results in induction of the tumor suppressor protein, p53, and the cyclin‐dependent kinase inhibitors, p21 and p27, as well as accumulation of hypophosphorylated pRb. Up‐regulation of p53 and p27 occurs by post‐transcriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
170
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(179 citation statements)
references
References 77 publications
7
170
2
Order By: Relevance
“…Analogous experiments performed with DG-75 lymphoma cells as negative controls revealed no induction of either the C͞EBP␣ or p21 proteins after TPA treatment (data not shown), suggesting that KSHV lytic infection was responsible for the up-regulation of both of these proteins. These results imply that, unlike the EBV lytic cycle trigger protein ZTA (also known as BELF1 or Zebra), which reportedly induces both p21 and p27 protein expression (25), KSHV RAP protein induces G 1 cell cycle arrest only through the p21 pathway.…”
Section: Expression Of C͞ebp␣ Is Increased After Lytic Cycle Inductiomentioning
confidence: 88%
See 2 more Smart Citations
“…Analogous experiments performed with DG-75 lymphoma cells as negative controls revealed no induction of either the C͞EBP␣ or p21 proteins after TPA treatment (data not shown), suggesting that KSHV lytic infection was responsible for the up-regulation of both of these proteins. These results imply that, unlike the EBV lytic cycle trigger protein ZTA (also known as BELF1 or Zebra), which reportedly induces both p21 and p27 protein expression (25), KSHV RAP protein induces G 1 cell cycle arrest only through the p21 pathway.…”
Section: Expression Of C͞ebp␣ Is Increased After Lytic Cycle Inductiomentioning
confidence: 88%
“…The EBV-encoded ZTA lytic transactivator protein also inhibits G 1 to S-phase cell cycle progression in lytically activated lymphoma cells by inducing the expression of the cyclindependent kinase inhibitors, p21 CIP-1 and p27 KIP (25,26). The KSHV-encoded RAP protein is evolutionarily related to ZTA and also contains a leucine zipper dimerization domain, but has no amino acid homology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…90 These data implied that Zta altered cell cycle progression through elevating levels of functional p53. It was also demonstrated that Zta-mediated G 0 /G 1 growth arrest was most readily observed in tumor cell lines expressing wild-type p53 and correlated with the posttranscriptional induction of p53.…”
Section: Zta As a Target Of Anticancer Therapymentioning
confidence: 90%
“…43 The 53BP1 itself can functionally regulate G2/M-phase DNA damage-activated cellcycle checkpoints after IR. 45,46 BZLF1 induces cell-cycle arrest in different cell lines, 47,48 and both G2 and mitotic block in HeLa cells. 49 As our study showed that BZLF1 could block the accumulation of 53BP1 and RNF8 proteins at the sites of DNA breaks, we further examined the effect of BZLF1 on IRinduced cell-cycle arrest.…”
Section: Bzlf1 Abrogates the G2/m Checkpoint And Increases Chromosomamentioning
confidence: 99%